Effect of frozen and refrozen storage of beef and chicken meats on inoculated microorganisms and meat quality. (May 2021) - Mohammed, Hammad Hamed Hammad; He, Lichao; Nawaz, Asad; Jin, Guofeng; Huang, Xi; Ma, Meihu; Abdegadir, Warda S.; Elgasim, Elgasim A.; Khalifa, Ibrahim
Abstract: The objective of this study was to investigate the effects of repeated freeze-thaw cycles on microorganisms, amino acid composition profile, chemical composition, mineral concentrations, water mobility, and fat of beef and chicken meats. Pure cultures of specific fungi and bacteria were separately injected into the minced meat. Apart from Pseudomonas, the total count of microorganisms significantly increased ( P  < 0.05) during refreezing treatment with the increase of storage period in both beef and chicken meats. During freezing treatment, the total count of Staphylococcus aureus, spore forming bacteria, and lactic acid bacteria were meat-type dependent. In conclusion, freeze-thaw cycles increased the microbial counts and decreased the water holding capacity, amino acids, and mineral concentrations of beef and chicken meats. Highlights: Both meat types had higher total bacterial count at the end of storage period in thawing conditions. Moisture and proteins were affected with increase of storage period in both meat types. Amino acids and minerals of beef and chicken meat were affected by microorganisms. Relaxation times were affected by bacteria in freeze-thaw storage conditions.